Nurses today – is this the dream of Florence Nightingale - Meera Saravanan; Naganandini Raju; Maheswari Kandhasamy; Annam Sengamali (International Journal Of Community Medicine And Public Health, 2026)
Florence Nightingale's enduring influence on contemporary nursing practice through a comprehensive analysis of her seminal work is "Notes on Nursing: What It Is, and What It Is Not" (1859). The study explores whether modern nursing fulfills Nightingale's original vision by comparing the foundational attributes she identified with the competencies required of today's nurses. Nightingale's core principles emphasized keen observation skills, common sense judgment, meticulous attention to cleanliness and hygiene, quiet demeanor, punctuality, organizational management, and genuine empathy for patients. These qualities, articulated over 160 years ago, remain remarkably relevant in contemporary healthcare settings. This review presents a detailed comparative analysis contrasting Nightingale's era with modern nursing across multiple dimensions including compassion and care, clinical skills, leadership, evidence-based practice, education, advocacy, work ethic, innovation, communication, courage, cultural awareness, and adaptability. Through eighteen clinical scenarios, the analysis demonstrates how Nightingale's principles translate into today's complex healthcare environments, from Intensive care and infection control to crisis management and end-of-life support. While technological capabilities and clinical interventions have advanced dramatically, the fundamental commitment to patient-centered care, environmental management, systematic observation, data-driven practice, and patient advocacy remains unchanged. The review concludes that Nightingale's vision of nursing as both an art requiring personal qualities and a science demanding systematic knowledge continues to shape excellence in contemporary nursing practice. Her legacy transcends historical significance, actively informing professional standards, educational requirements, infection control protocols, and the ethical foundation of modern nursing, proving that her pioneering principles remain vital to quality patient care in the 21st century.